Community experiences in health for integration University and Pío Tamayo community. (Revista Venezolana de Salud Pública, 2018)
The present study, aims to integrate community experiences in Health of theUniversity and Community "Pio Tamayo" to generate social changes in the context of study.
Keywords: Experience; integration; University; Community; investigation action